Economic process optimization deployed by companies with complex activity production – trade – services using informatics systems with integrated data mining techniques - ANDRONIE, Mihai (Annals of Spiru Haret University. Economic Series, 2010)
There are many economic processes deployed by companies with a complex activity that can be optimized, among the most common being: supply, production/service, distribution, sales, suppliers/customers relationships, inventory management, human resources management, financial management, etc. After the deployment of business processes related data is obtained. The analysis of the related data must be the starting point in any attempt to optimize the economic processes because this data best reflects the actual situation of the company. In order to carry out such an analysis, several approaches have emerged to extract knowledge from the data accumulated. The first solution is to use specific software to analyze the available data. Another solution that can be successfully used is the implementation of data mining techniques within the database management software available supposing it is a new generation one.